Application of Mir-301a in the prediction of chemosensitivity and evaluation of the effect of neoadjuvant chemotherapy in gastric cancer - Chao Yan; Jian-Chun Yu (临床与病理杂志, 2026)
Objective: Previous research has revealed an elevated expression of miR-301a in gastric cancer. Our study aimed to explore the potential role of miR-301a as a biomarker for predicting the chemosensitivity and evaluating the effect of NAC in gastric cancer. Methods: The expression levels of circulating miR-301a in plasma of 50 patients with advanced gastric cancer were assessed before and after NAC, as well as in 50 healthy individuals. The correlations between miR-301a and clinicopathological features, traditional measures like CT, EUS and tumor markers were also analysed. Results: MiR-301a showed a higher expression in patients’ plasma than healthy individuals (P=0.01). The expression was significantly associated with NAC sensitivity (P=0.006) and tumor downstaging (P=0.002). After NAC, significant decreased miR-301a levels are often accompanied by preferable tumor remission, showing a better NAC sensitivity. Meanwhile, the traditional measures (CT, EUS, tumor markers) showed much less accuracy comparing with miR- 301a. Conclusion: Our results indicate that plasma miR- 301a may be a potential biomarker for evaluating the effect of NAC and predicting chemoresistance in gastric cancer.